Comparing disfluency on words and nonwords in children who stutter - Seyed Abolfazl Tohidast; Mohammad Rahim Shahbodaghi; Banafsheh Mansuri; Shohreh Jalaei (Vesnu Publications, 2013)
Introduction: Stuttering is a multidimensional disorder which may be affected by many factors including linguistic aspects. The aim of this study was to investigate the frequency of disfluencies over words and nonwords in children who stutter. Materials and Methods: 15 children with stuttering, whose age ranged from 4 to 5 years, participated in this descriptive-analytical study. They were asked to repeat words and non-words that they heard while their utterances were recorded. The statistical analysis was conducted in SPSS. Results: Disfluency frequency was significantly higher on repeating words than on repeating nonwords (P < 0.05). Common disfluencies were of repetition and block types. Conclusion: According to the results of the present study, linguistic complexities can increase the occurrence of disfluency frequency. Keywords: Words, Nonwords, Disfluency, Children who stutter